Quantum phase transition and non-Fermi liquid behavior in Fe1−xCoxSi (x ⩾ 0.7). (14th March 2018) - Samatham, S Shanmukharao; Suresh, K G; Ganesan, V
Abstract: We report on the nature of electron correlations in Fe1− x Co x Si ( 0.7 ⩽ x < 1 ) using combined results of magnetization, specific heat and transport properties. Doping driven quantum critical point is observed to occur at x ∼ 0.75 . The magnetically unstable regime is identified to be centered around x ∈ [ 0.75, 0.95 ]. The emergence of non-Fermi liquid behaviors in x = 0.8 (near to ferromagnetic quantum critical point) and x = 0.9 (disorder-induced) compositions are discussed on the basis of the power-law dependence of susceptibility χ ∼ T − g ( g ∼ 1.07 for x = 0.8 and 0.55 for x = 0.9), specific heat C / T ∼ T − 1 + λ ( λ ∼ 1.52 for x = 0.8 and 0.9) and resistivity Δ ρ ∼ T d ( d ∼ 1.56 for x = 0.8 and 1.38 for x = 0.9). Further, a comprehensive classification of doping dependent physical properties of Fe1− x Co x Si is presented in the revisited temperature-composition ( T - x ) phase diagram.